Increased Risk of Preterm Premature Rupture of Membranes at Early Gestational Ages among Maternal Cigarette Smokers - England, Mary C.; Benjamin, Alice; Abenhaim, Haim A. (American Journal of Perinatology, 2013)
Objective To examine the effect of cigarette smoking during pregnancy on the development of preterm premature rupture of membranes (PPROM) categorized by gestational age.Methods We conducted a retrospective cohort study of 17,961 births using data from the McGill Obstetric and Neonatal Database between years 2001 and 2006. Our exposure was defined according to self-reported maternal cigarette smoking status categorized as nonsmoker, smoker of 1 to 10 cigarettes per day, and smoker of > 10 cigarettes per day. The outcome was measured as incidence of premature rupture of membranes (PROM) among gestational age categories of < 28, < 32, < 37, and > 37 weeks. Unconditional logistic regression analysis and Wald test for trend were used to estimate the adjusted risk of PPROM according to smoking status.Results Among the study population, 640 cases of PPROM (<37 weeks) and 40 cases of PROM (>37 weeks). After adjusting for confounding variables, smoking > 10 cigarettes per day was associated with an increased risk of PPROM at < 28 weeks (odds ratio [OR] 5.28; 95% confidence interval [CI] 2.20 to 12.7); < 32 weeks (OR 2.36; 95% CI 1.09 to 5.11; < 37 weeks (OR 1.97; 95% CI 1.32 to 2.94); and > 37 weeks (OR 3.19; 95% CI 0.92 to 11.0). Smoking 1 to 10 cigarettes per day was not associated with a significant risk of PPROM at any gestational age.Conclusion Heavy cigarette smoking increases the risk of PPROM more so at early gestational age than at term.
Keywords: cigarette smoking; premature rupture of membranes; gestational age